Public osteomyelitis caused by Staphylococcus simulans. Issue 818 (December 1993) - Sturgess, I.; Martin, F.C.; Eykyn, S.
Abstract : A patient is described who developed pubic osteomyelitis caused by an uncommon pathogen, Staphylococcus simulans.